GEOSTATIONARY SATELLITE NAVIGATION SYSTEMS: A REVIEW - Dr. Pijush Kanti Tripathi (The Bioscan, 2024)
Nuclear power and renewable energy are two of the world's most popular energy sources. However, reducing pollution and combating climate change require a shift to greener energy sources like nuclear power and bioenergy. An overview of the effects of various energy sources on pollution is given in this review, which also looks at how they affect the quality of the air, water, and soil in addition to how they influence climate change. This review also gives an overview of how these energy sources affect human health and ecosystems.